The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41598-022-16053-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac rehabilitation may influence leptin and VEGF A crosstalk in patients after acute coronary syndrome

Abstract: Leptin, a well-proven cardiovascular risk factor, influences vascular endothelial growth factor A (VEGF A) synthesis via hypoxia-inducible factor 1 alpha (HIF-1A), nuclear factor kappa-light-chain-enhancer of activated B cells (NfkB) and NILCO (Notch, interleukin 1 [IL1] and leptin cross-talk outcome) pathways. This study aimed to investigate the influence of cardiac rehabilitation (CR) on HIF-1A, NfkB and NILCO dependent leptin and VEGF A cross-talk in patients after acute coronary syndrome (ACS). Fifty post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In the study of Alqaderi et al, levels of leptin and VEGF in saliva were found not to be good predictors of obesity or hyperglycemia in adolescents 123 . Our own studies have shown that cardiac rehabilitation can decrease serum leptin and HIF‐1A levels in patients who have undergone acute coronary syndrome 124 …”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…In the study of Alqaderi et al, levels of leptin and VEGF in saliva were found not to be good predictors of obesity or hyperglycemia in adolescents 123 . Our own studies have shown that cardiac rehabilitation can decrease serum leptin and HIF‐1A levels in patients who have undergone acute coronary syndrome 124 …”
Section: Resultsmentioning
confidence: 68%
“…[112][113][114][115] Studies of patients with obesity have confirmed the genetic or epigenetic aspect of leptin-VEGF crosstalk, pointing to the role of obesity-dependent leptin gene regulation. [104][105][106][107] These studies have also revealed that leptin-VEGF crosstalk is a complicated network, involving leptin canonical and noncanonical signaling pathways, HIF-1A, and NfkB as the core, 97,124,136 with a range of substances (including adiponectin, visfatin, ghrelin, IL-6, insulin, cholesterol, LDL, triglycerides, ApoB, trimethylamine N-oxide, and NO) acting as accompanying, modifying, and disrupting factors. [99][100][101] In female patients with excess body mass and related disorders, leptin-VEGF crosstalk may be involved in PCOS, adverse pregnancy outcome, 129 and preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these studies proved that PWV is one of the key factors influencing cardiovascular risk in patients with subclinical MetS. Recently, Skrypnik et al indicated that the implementation of the cardiac rehabilitation programme can lead to a decrease in serum leptin levels [14], which can influence arterial stiffness [15].…”
Section: Discussionmentioning
confidence: 99%